2023
DOI: 10.1002/adfm.202304974
|View full text |Cite
|
Sign up to set email alerts
|

Shining Light on Multidrug‐Resistant Bacterial Infections: Rational Design of Multifunctional Organosilver‐Based AIEgen Probes as Light‐Activated Theranostics for Combating Biofilms and Liver Abscesses

Abstract: The intricate environment of biofilms provides a heaven for bacteria to escape antibiotic eradication, leading to persistent chronic infections. Therefore, it is urgently needed to develop effective therapies to combat biofilm‐associated infections. To address this problem, a series of antimicrobial agents are designed and synthesized utilizing triphenylamine imidazole silver complexes (TPIMS). Due to the photoactivated release of Ag+ coupled with aggregation‐induced emission (AIE) properties and efficient 1O2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…The antimicrobial power of Ag is mainly expressed by the form of Ag + . Ag + is able to enter the cytoplasm of bacteria and exert its antimicrobial action by interfering with the function of a variety of proteins and enzymes and restraining the synthesis of nucleic acids and proteins, leading to bacterial death, and Ag nanomaterials also function as antimicrobials by releasing Ag + ( Eliaz and Metoki, 2017 ; Wei et al, 2020 ; Liu et al, 2023 ). Another significant mechanism by which Ag kills bacteria is direct contact killing.…”
Section: Antimicrobial Coatingsmentioning
confidence: 99%
“…The antimicrobial power of Ag is mainly expressed by the form of Ag + . Ag + is able to enter the cytoplasm of bacteria and exert its antimicrobial action by interfering with the function of a variety of proteins and enzymes and restraining the synthesis of nucleic acids and proteins, leading to bacterial death, and Ag nanomaterials also function as antimicrobials by releasing Ag + ( Eliaz and Metoki, 2017 ; Wei et al, 2020 ; Liu et al, 2023 ). Another significant mechanism by which Ag kills bacteria is direct contact killing.…”
Section: Antimicrobial Coatingsmentioning
confidence: 99%
“…1–5 Biofilms, formed by bacteria that adhere to surfaces and aggregate together within a matrix of extracellular polymeric substances (EPS), create a formidable barrier to effective anti-bacterial treatments and evade the host immune system. 6–10 The formation of biofilms further exacerbates the severity of MRSA infections. It is well demonstrated that the encapsulation of EPS creates an oxygen-deficient biofilm microenvironment, which can lead to anaerobic glycolysis.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 In recent years, photodynamic therapy has gradually entered the clinical treatment of bacterial infections due to its advantages of low dark toxicity, high selectivity and low risk of bacterial resistance. [13][14][15][16] However, for wound infections caused by Gram-negative bacteria, some small-molecule photosensitizers are unable to impart the expected effect due to the inability to counteract the outer membrane barrier. Fortunately, antimicrobial peptides (AMPs), which have a destructive effect on the bacterial surface, impart a synergistic antimicrobial effect with photosensitizers.…”
Section: Introductionmentioning
confidence: 99%